Peningkatan pengetahuan bagi siswa tentang makanan jajanan sehat dan pola hidup sehat melalui olahraga kesehatan - Pajar Annugrah Prasetio; Febby Fajar Nugraha; Galih Dani Septiyan Rahayu (IKIP SILIWANGI, 2024)
In our lives, of course, humans really need adequate nutrition obtained from the food we consume every day, especially at a growing age such as children, children's nutrition must be adequate and fulfilled in terms of nutritional content. The issue of nutritional problems is often a problem that receives little attention. Behavior is determined by knowledge factors (Notoatmodjo 2014). By knowing the characteristics of unhealthy snacks, children can avoid consuming additives that are harmful to the body. Moreover, there are many phenomena among children, especially of school age, especially at the elementary school level, there are still many children who often snack on food/snacks, which of course are made from food ingredients. If you pay attention, there are many snacks that are not good for children, for this reason it is necessary there is intensive guidance to children, parents and teachers regarding these snack habits. The methods used in this Pkm are lecture, practice/simulation and question and answer methods involving upper class students. The result of this method is an increase in the average value of knowledge about healthy snacks and healthy lifestyles among students. It is hoped that this result will make students' behavior more careful in choosing healthy snacks and implementing a healthy lifestyle.